Discover the patterns of prepaid mobile phone user to predict the customer behavior for marketing strategy / Wan Nuradlina Wan Ismail - Wan Ismail, Wan Nuradlina (2005)
The way in which telecommunication companies interact with their customers has changed dramatically over the past few years. A customer's loyalty to a certain telecommunication company is no longer guaranteed. The telecommunication companies must deal with a large amount of competitors. To succeed, telecommunication companies must be proactive and anticipate what customer desires. It was found that telecommunication companies need to understand their customers well and to quickly feedback to them wants and needs in order to success. The objectives of this research are to discover the patterns of prepaid mobile phone user using SPSS as one of the method in data mining and to predict the customer behavior for marketing strategy. In this research, primary and secondary resources are used in order to fulfill the research objectives. Primary data are collected through the distribution of questionnaire. The questionnaire consists of 29 questions and was distributed to the prepaid mobile phone users in Shah Alam. The total of 100 questionnaires was collected within two-week period. While secondary data is taken from journals and Internet resources. All data gathered from this research were analyzed using SPSS version 12.0 software. Data were presented in the form of frequency distribution tables for selected variables and via graphical presentation like bar and pie charts. From the research conducted, majority of the prepaid user are student. Most of them subscribed to Maxis the their family also subscribe to Maxis. Most of the users choose to subscribe to the same operator as their families subscribe to. Majority of the user prefer to use SMS rather than make a phone call. Majority of the user spend above RM50 a month to reload the credit. Most of the user likes to travel as their leisure activities. They also like to go shopping and watching movies. Most of the users choose which mobile operators to subscribe to because of the call and SMS rate charge by the operator, network coverage of the mobile operator, promotions and innovative services provided by the mobile operator.